Foreign direct investment and poverty reduction - Mercy Tsitsi Magombeyi; Nicholas M. Odhiambo (Comparative Economic Research. Central and Eastern Europe, 2017)
This paper provides a detailed survey of the literature on the impact of foreign direct investment (FDI) on poverty reduction, outlining the theoretical and empirical relationship between these variables. Although a number of studies have been done on the impact of FDI on poverty reduction, the majority of these studies have focused on the indirect impact of FDI on poverty reduction. The bulk of the literature reviewed supports the positive effects of foreign direct investment on poverty reduction, although a few studies have also found foreign direct investment to have an adverse or insignificant effect on poverty reduction. This study differs fundamentally from previous studies in that it focuses on the direct impact of FDI on poverty reduction, giving a detailed review of the nature of this relationship.
Keywords: I3; O1; 330; Foreign direct investment; poverty reduction; dynamic impact